2008
DOI: 10.1016/s1808-8694(15)31087-9
|View full text |Cite
|
Sign up to set email alerts
|

Speech recognition thresholds in noisy areas: Reference values for normal hearing adults

Abstract: The phrases recognition thresholds in the free fields were obtained in the signal to noise ratio of -8.14 dB H, which is the reference value for normal hearing individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The evaluations were carried out in a soundproof room, with the subjects wearing hearing aids fitted in accordance with the data taken from their individual audiometric tests and positioned one meter away from the sound source placed on 0° azimuth, i.e., in front of the subjects. In order to obtain free field sound pressure levels, measurements were made as per the procedure described in previous studies 17 .…”
Section: Methodsmentioning
confidence: 99%
“…The evaluations were carried out in a soundproof room, with the subjects wearing hearing aids fitted in accordance with the data taken from their individual audiometric tests and positioned one meter away from the sound source placed on 0° azimuth, i.e., in front of the subjects. In order to obtain free field sound pressure levels, measurements were made as per the procedure described in previous studies 17 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the literature report that even normal hearing people complaint about the difficults to understand other inside a noisy enviroment. (27) Hence, communication between family and professionals in the NICU with elevated SPL could be impaired and, as a result, many important information are lose, which might cause conflicts between parents and professionals and also promotes a less humanized environment.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Thus, the tests chosen by different lists of clinical conditions are of great importance because they allow an analysis of the comprehension of the spoken message in circumstances close to the communication conditions that you encounter in your daily life. 5 To understand the role of cognition in the intelligibility of oral language, one of the pillars of cognition must be considered, the concept of working memory.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Thus, it is observed that the basic audiological assessment, which involves obtaining pure tone auditory thresholds and tests with isolated words, does not make it possible to infer the communicative capacity of each individual as monosyllabic words, which are reproduced at uniform levels of presentation and do not suffer the effects of co-articulation, are not representative of the everyday speech to which the patient is exposed in everyday communication situations. 3,4 Thus, the tests chosen by different lists of clinical conditions are of great importance because they allow an analysis of the comprehension of the spoken message in circumstances close to the communication conditions that you encounter in your daily life. 5 To understand the role of cognition in the intelligibility of oral language, one of the pillars of cognition must be considered, the concept of working memory.…”
Section: Introductionmentioning
confidence: 99%